Programmed cell death-ligand 1 expression in correlation with human papillomavirus status in cervical cancer: A 1-year retrospective study - Kaumudi Konkay; Padmavathi Devi Chaganti; Radhika Medidi; Ann Mary Varghese; Maruthi Devi Karri (Journal of Clinical and Scientific Research, 2025)
Background: Programmed cell death-ligand 1 (PD-L1) is an immunosuppressive molecule which regulates T-cell activation. The objective of the study was to enumerate PD-L1 expression profile of cervical carcinoma and correlate it with various histopathological features along with human papillomavirus (HPV) status. Methods: This was a hospital-based retrospective study of 1-year duration. Records of patients with cervical cancer were reviewed, and 40 cases were taken for tissue microarray. Immunohistochemistry with p16 and PD-L1 was done, and association between PD-L1 expression with age, histopathological features and HPV status was studied. Results: PD-L1 was positive in 2 (2b), low positive (LP) in 14 and score 1a = 10, 1b = 4 and negative = 24 cases. Squamous cell carcinomas (SCCs) (n = 36), PDL-1 was positive in 2, LP 12 and negative in 22. HPV associated [HPVA] tumours were 36 and HPV independent [HPVI] tumours were 4. PD-L1 expression was more in HPVA (15/36, 41.6%) than HPVI (1/4). Adenocarcinoma (n = 1) was PD-L1 LP (1a) and HPVA. Adenosquamous carcinomas (n = 2), both were negative for PDL-1 and were HPVA. Small-cell neuroendocrine carcinoma (n = 1) was PDL-1 positive (1b) and HPVA. Conclusion: PD-L1 expression was 40% and was independent of morphology and grade, more commonly associated with HPV.